Penerapan Algoritma Lzy Untuk Mengkompresi Record Dalam Merancang Aplikasi Kamus Besar Bahasa Indonesia - Zein Maulana, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Dictionary is a medium that can be interpreted as a book that contains the meaning of a word from a foreign language or term, the dictionary is also a large container of knowledge and knowledge, especially language knowledge. Dictionary should be one application that must be owned by every smartphone user. However, the size of the application is quite large so it requires a large enough storage space as well. Limited storage space or free space on smartphones makes users have to be willing to sacrifice other data to be deleted in order to install the dictionary application. Data compression or compression is one method to reduce data storage space on a storage medium, data compression aims to reduce the number of bits used in data storage or transmission. Data compression is carried out due to limited memory space, and limited storage space. To produce the smallest ratio size with a fast process, in this study the algorithm used is the LZY algorithm which is considered capable enough to overcome the above problems.